ปัญหาและแนวทางการพัฒนาการบริหารงานวิชาการ โรงเรียนจุฬาภรณราชวิทยาลัย สตูล (โรงเรียนวิทยาศาสตร์ภูมิภาค) สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 16 - คงอินทร์, วิไลพร; ธีระวณิชตระกูล, สฎายุ; รักงาม, ชัยพจน์ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 27 No 3 (2559): Academic Services Journal, Prince of Songkla University, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาปัญหาและแนวทางการพัฒนาการบริหารงานวิชาการโรงเรียนจุฬาภรณราชวิทยาลัย สตูล (โรงเรียนวิทยาศาสตร์ภูมิภาค) สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 16 เป็นงานวิจัยเชิงคุณภาพ ภายใต้โครงสร้างการบริหารงานวิชาการโรงเรียนจุฬาภรณราชวิทยาลัย สตูล ใน 5 ด้าน คือ ด้านงานกลุ่มสาระการเรียนรู้ ด้านการพัฒนาหลักสูตร ด้านกิจกรรมพัฒนาผู้เรียน ด้านงานแนะแนว และด้านวิทยบริการ การเก็บรวบรวมข้อมูลแบ่งออกเป็น 2 ส่วน คือ ใช้การสัมภาษณ์เชิงลึก (In-depth interviews) เพื่อทราบปัญหาการบริหารงานวิชาการ จากผู้บริหาร คณะกรรมการสถานศึกษา หัวหน้างาน หัวหน้ากลุ่มสาระการเรียนรู้ ครู ผู้ปกครอง และนักเรียน จำนวน 38 คน จากนั้นใช้การสนทนากลุ่ม (focus group) เพื่อหาแนวทางการพัฒนาการบริหารงานวิชาการจากผู้เชี่ยวชาญ จำนวน 10 คน ผลการวิจัยพบว่า 1. ปัญหาการบริหารงานวิชาการโรงเรียนจุฬาภรณราชวิทยาลัย สตูล พบว่า ด้านที่มีปัญหามากที่สุดคือ ด้านงานกลุ่มสาระการเรียนรู้ คือ การจัดตารางเรียนตารางสอน ครูสอนไม่ตรงตามประสบการณ์ ไม่มีการบูรณาการชิ้นงาน บรรยากาศในชั้นเรียนไม่เอื้อต่อการเรียนรู้ รองลงมา คือ ด้านวิทยบริการ แหล่งเรียนรู้ทั้งภายในและภายนอกมีไม่เพียงพอ และไม่มีแหล่งเรียนรู้จากภูมิปัญญาท้องถิ่น ด้านการพัฒนาหลักสูตร หลักสูตรไม่สอดคล้องกับท้องถิ่น ไม่มีการประชาสัมพันธ์ให้ชุมชนมีส่วนร่วมในการทำหลักสูตร เทคนิคการสอนของครูไม่หลากหลาย การจัดแผนการจัดการเรียนรู้ไม่มีเอกภาพ ด้านกิจกรรมพัฒนาผู้เรียน กิจกรรมไม่หลากหลายไม่ตรงตามความสนใจและความถนัดของผู้เรียน และด้านงานแนะแนว บุคลากรไม่เพียงพอ บุคลากรที่จบโดยตรงมีน้อย ภาระงานเยอะ ตามลำดับ 2. แนวทางการพัฒนาการบริหารงานวิชาการ พบว่า ด้านงานกลุ่มสาระการเรียนรู้ ควรจัดทำตารางเรียนตารางสอนพร้อมกันระหว่างครูและหัวหน้ากลุ่มสาระการเรียนรู้ ควรส่งเสริมให้ครูได้รับการพัฒนา โดยการอบรมแลกเปลี่ยนเรียนรู้ในรายวิชาที่ไม่มีความถนัด จัดให้มีการประชุมวางแผนการบูรณาการชิ้นงานของครูในทุกวิชา จัดบรรยากาศในชั้นเรียน และซ่อมบำรุงอุปกรณ์ให้ใช้งานได้อยู่เสมอ ด้านวิทยบริการ ควรสำรวจแหล่งเรียนรู้เพิ่มเติม กลุ่มสาระการเรียนรู้ทุกกลุ่มสาระควรมีห้องสมุด และนำภูมิปัญญาท้องถิ่นมาใช้ประโยชน์ในการทำโครงงาน ด้านการพัฒนาหลักสูตร มีการนำหลักสูตรท้องถิ่นมาบูรณาการในการจัดการเรียนการสอน มีการประชาสัมพันธ์ให้ท้องถิ่นมีส่วนร่วมในการทำหลักสูตร ส่งเสริม สนับสนุนให้ครูผู้สอนได้พัฒนาตนเองเรื่องเทคนิคการสอน ประชุมวางกรอบการจัดทำแผนการจัดการเรียนรู้ ด้านกิจกรรมพัฒนาผู้เรียน ควรสำรวจความต้องการ ความสนใจของผู้เรียน ใช้ระบบสภานักเรียนในการขับเคลื่อนเพื่อให้เกิดกิจกรรม สำรวจและพัฒนาแหล่งเรียนรู้ทั้งภายในและภายนอกให้มีความสอดคล้องกับความต้องการและทันสมัยอยู่เสมอ ด้านงานแนะแนว ควรส่งเสริมให้ครูในโรงเรียนทุกคนมีความรู้ความเข้าใจในงานแนะแนว ให้ครูแนะแนวเป็นผู้บริหารงานแนะแนว จัดกระบวนการเรียนการสอน คำสำคัญ: ปัญหาและแนวทางการพัฒนา, การบริหารงานวิชาการ, โรงเรียนจุฬาภรณราชวิทยาลัย สตูล   This qualitative research aimed to study the problems and guideline solutions to academic administration of Princess Chulabhorn’s College, Satun under The Secondary Educational Service Area Office 16. The research covered 5 sections of the academic administration structure of Princess Chulabhorn’s College, Satun: 1) teaching and learning, 2) curriculum development, 3) student development, 4) counseling and guidance, and 5) the academic resource center. The data collection was divided into two parts as follows. First, in-depth interviews were used to uncover the problems concerning the academic administration. A total of thirty-eight individuals from the administrators, the school committee members, heads of all departments, teachers, parents and students were involved in the interview. Second, the group discussion (focus group) was conducted with 10 experts to consider possible guidelines for academic administration development. The results showed that the teaching and learning section was the most problematic, particularly with the teaching and learning schedule, inexperienced teachers, non-integrated tasks, and unsupportive classroom atmosphere. Next, the academic resource center provided insufficient external and internal learning resources as well as insufficient local wisdom resources. Curriculum development was not consistent with local socio-economic development. Also, the locals hardly took part in the curriculum development. The teaching techniques were not diverse, and the teaching plans were not united. The student development affairs did not provide diverse activities, nor reach students’ interests and aptitudes. Lastly, the school lacked enough experienced and qualified staff working in the Student Counseling and Guidance Department. Possible guidelines for academic administration development were proposed as follows: teaching and learning schedules should be managed based on agreements among teachers and their heads. Teachers should be more encouraged to develop their teaching methods—especially those of the subjects they are not specialized in, to plan integrated tasks with all other related subjects, and to manage the classroom atmosphere and always maintain all the equipment in the classroom. The academic resource center should explore and provide additional resources. It was suggested that all the main departments supply small, specified libraries or resource corners. To achieve government policy in developing the school curriculum, local wisdom should be utilized for students’ scientific projects and be integrated in teaching and learning activities of all related subjects. The local community should take part in the curriculum development. Course syllabus and lesson plans should be agreed upon by all related individuals. Student development affairs should conduct a survey of students’ needs and interests, which should be proceeded by the student council. It was essential to survey new internal and external resources and develop and modernize them to suit the needs and interests of the students. As the Student Counseling and Guidance Department does not have enough qualified staff, other teachers should understand and assist with the work and tasks of the Student Counseling and Guidance Department. Keywords: problems and development, academic administration, Princess Chulabhorn’s College, Satun